OUTCOMES OF MINIMALLY INVASIVE PLATE OSTEOSYNTHESIS (MIPO) FOR DIAMETAPHYSEAL DISTAL TIBIA FRACTURES AT KOSHI ZONAL HOSPITAL - Roshan Yadav; Shambhu Sah; Nabin Subedi; Yagya Kharel; Mahendra Mahato; Shilabant Sen Sribastav; Diwas Raj Bhandari (Medico Research Chronicles, 2020)
Introduction: Lower limb trauma is a common presentation in our day to day clinical practice. Distal diametaphyseal tibia being subcutaneous bone is one of the common fracture sites. Open reduction and internal fixation (ORIF) could further endanger their circulation adding iatrogenic trauma. Closed reduction and minimally invasive plate osteosynthesis (MIPO) with pre-contoured locking plate on basis of biological osteosynthesis (BO) is an alternative treatment option. The aim of this study is to estimate hospitalization period, fracture union period and complications of MIPO with pre-contoured locking plate on diametaphyseal distal tibia fracture. Objective: Evaluation of outcomes after MIPPO in distal diametaphyseal fractures managed by using distal tibial pre-contoured locking plate at Koshi Zonal Hospital. Methodology: Twenty-seven patients with close distal tibia diametaphyseal fracture were treated with MIPO technique between May 2016 to June 2018 in Koshi Zonal hospital. Results: There were 27 patients with mean age 43.83 years ( range: 18- 70 years). The average duration of hospital stay was 11.94 days (range: 6-25 days). Average fracture union duration was 21.05 weeks (range:17-27weeks); among them, two cases got a superficial infection. There was no angulation and no implant failure. Eight patient complained implant prominence and pain around ankle after fracture healed. Conclusion: MIPO with pre-contoured locking plating in distal tibia diametaphyseal fracture is a rational choice with short union time, few complications and early rehabilitation.